Creosote Bush (Larrea tridentata) Improves Insulin Sensitivity and Reduces Plasma and Hepatic Lipids in Hamsters Fed a High Fat and Cholesterol Diet - Del Vecchyo-Tenorio, Georgina; Rodríguez-Cruz, Maricela; Andrade-Cetto, Adolfo; Cárdenas-Vázquez, René (Frontiers in Pharmacology, 2016)
Creosote bush, Larrea tridentata (Sesse y Moc. Ex DC, Zygophyllaceae) is a shrub found in the deserts of Northern Mexico and Southwestern United States. In traditional medicine, it is used to treat a variety of illnesses including type 2 diabetes. The present study aims to investigate the effects of creosote bush ethanolic extract on plasma and liver parameters associated with the metabolic syndrome in hamsters fed a high fat and cholesterol diet (HFD), comparing them with those induced by ezetimibe. Seven groups of 6 hamsters each were formed. Six groups were fed HFD for two weeks. The following 2 weeks, the HFD groups received: 1) only HFD, 2) HFD + 3mg% ezetimibe, 3) HFD + 0.2% creosote bush ethanolic extract , 4) only standard diet (Std Diet), 5) Std Diet + 3mg% ezetimibe, 6) Std Diet + 0.2% creosote bush ethanolic extract. The beneficial effects of creosote bush ethanolic extract in the HFD hamster model were a reduction of insulin resistance, associated with lower serum insulin and leptin, lower hepatic lipid peroxidation and higher liver antioxidant capacity. Plasma and liver lipids tended or were reduced to values closer to those of animals fed standard diet. A similar effect on lipids was induced by ezetimibe, although with even lower hepatic cholesterol and total lipids concentrations. In general, the change from HFD to standard diet plus ethanolic extract induced the same but deeper changes, including a reduction in plasma glucose and an increase in the percentage of HDL cholesterol. Unlike creosote bush extract, ezetimibe increased food consumption and neutral fecal steroids, with no significant effect on body weight, epididymal fat pads, liver peroxidation or antioxidant capacity. Also ezetimibe did not modify serum insulin and leptin. However, insulin sensitivity improved to values similar to those induced by the extract. This suggests that the mechanism of action of creosote bush ethanolic extract is different to inhibition of cholesterol absorption or increase excretion. The ethanolic extract of Larrea tridentata could be useful in the treatment of the metabolic syndrome.